Greek thinkers: a history of ancient philosophy - Gomperz, Theodor (J. Murray, 1906)
Vol. I. book I. The beginnings. book II. From metaphysics to positive science. book III. The age of enlightenment.-- vol. II. book IV. Socrates and the Socratics. book V. Plato. -- vol. III. book V. (continued) Plato.-- vol. IV. book VI. Artistole and his successors.